2013
DOI: 10.5664/jcsm.2344
|View full text |Cite
|
Sign up to set email alerts
|

First Night Effect Analysis in a Cohort of Young Children with Autism Spectrum Disorder

Abstract: Study Objectives: To evaluate for the fi rst night effect (FNE) in a group of young children with autism. Design: Analysis of polysomnographic data from a 2-night sleep laboratory study. Setting: Clinical Center of the National Institutes of Health. Patients or Participants: 15 children (aged 2-10 years) with a diagnosis of an ASD. Interventions: None. Measurements and Results: Polysomnographic analysis showed the presence of a FNE for wake after sleep onset minutes, stage 2, and sleep effi ciency, but not for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
(27 reference statements)
1
14
0
Order By: Relevance
“…Hering et al 31 reported 1 child in the autistic group on carbamazepine. 61 For this reason, all but 2 of the studies using PSG excluded the first night from analysis. Souders et al did not require children to be medication free and included children on medications to treat allergies, asthma, and gastrointestinal complaints, as well as stimulant medications, SSRIs, atypical neuroleptics, anticonvulsants, and medications to aid sleep such as melatonin and clonidine.…”
Section: Establishment Of Asd Diagnosismentioning
confidence: 99%
“…Hering et al 31 reported 1 child in the autistic group on carbamazepine. 61 For this reason, all but 2 of the studies using PSG excluded the first night from analysis. Souders et al did not require children to be medication free and included children on medications to treat allergies, asthma, and gastrointestinal complaints, as well as stimulant medications, SSRIs, atypical neuroleptics, anticonvulsants, and medications to aid sleep such as melatonin and clonidine.…”
Section: Establishment Of Asd Diagnosismentioning
confidence: 99%
“…The nature of the sleep disturbances varies across patients, but includes decreased total sleep [2935], increased sleep latency [26,29,3640], more fragmented sleep/decreased sleep efficiency [36,3842], increased stage non-rapid eye movement 1 (N1) sleep [38,40], decreased slow-wave sleep (SWS) [38,40], decreased rapid eye movement (REM) sleep latency [31,35] and decreased REM sleep [33,34,41]. …”
Section: Disturbances Of Sleep In Neurodevelopmental Disordersmentioning
confidence: 99%
“…Previously, SE has been shown to decrease, TST shorten, WASO increase, and SL and REM latency lengthen during a first PSG night in populations aged 2-93 years (Buckley et al, 2013;Curcio et al, 2004;Kis et al, 2014;Moser, Kloesch, Fischmeister, Bauer, & Zeitlhofer, 2010;Newell et al, 2012;Prihodova et al, 2010;Scholle et al, 2003;Toussaint et al, 1995;Wauquier et al, 1991;Zheng et al, 2012). Tamaki et al 2005) also showed a slower and more fragmented sleep onset during a first night in a sleep laboratory.…”
Section: Discussionmentioning
confidence: 86%